2017
DOI: 10.12659/msm.905739
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-Akt Signal Transduction Molecules Maybe Involved in Downregulation of Erythroblasts Apoptosis and Perifosine Increased Its Apoptosis in Chronic Mountain Sickness

Abstract: BackgroundChronic mountain sickness (CMS) has a higher incidence in the plateau region. The one of its principal characters is excessive erythrocytosis. The PI3K-Akt pathway plays an important role in the process of erythropoiesis, and could downregulate apoptosis by regulating apoptosis-related molecules. In this paper, we explored the change in apoptosis of erythroblasts and the effect of the PI3K-Akt signal pathway on erythroblasts apoptosis in CMS.Material/MethodsA total of 22 CMS and 20 non-CMS participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Therefore, Akt and SGK3 might be other signaling proteins besides ER stress that can promote PERK activation in CMS neurons after hypoxia treatment. Interestingly, CMS bone marrow mononuclear cells were reported to have an increased Akt expression that promotes erythroblasts survival and decreases apoptosis in CMS patients with excessive erythrocytosis ( Zhao et al, 2017a ). The differences of Akt expression between neurons and bone marrow mononuclear cells in the two studies might be tissue-specific, since CMS patients have distinguishable tissue specific pathologies, namely in the central nervous system and in red blood cells ( Azad et al, 2016 ; Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Akt and SGK3 might be other signaling proteins besides ER stress that can promote PERK activation in CMS neurons after hypoxia treatment. Interestingly, CMS bone marrow mononuclear cells were reported to have an increased Akt expression that promotes erythroblasts survival and decreases apoptosis in CMS patients with excessive erythrocytosis ( Zhao et al, 2017a ). The differences of Akt expression between neurons and bone marrow mononuclear cells in the two studies might be tissue-specific, since CMS patients have distinguishable tissue specific pathologies, namely in the central nervous system and in red blood cells ( Azad et al, 2016 ; Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akt is a pro-survival signaling protein and the PI3K/Akt/mTORC pathway cross links with both ER stress and autophagy ( Qin et al, 2010 ; Kabir et al, 2018 ). In CMS patients, the Akt gene is shown to associate with chronic mountain sickness ( Buroker et al, 2017 ) and plays an important role in regulating apoptosis in CMS patients with excessive erythrocytosis ( Li et al, 2017 ; Zhao et al, 2017a ). Therefore, in the current study, we explored the relationship between mitochondria and ER stress in iPSCs-derived CMS neurons and non-CMS neurons and investigated the potential rescue role of Akt from progression to hypoxia-induced cell death in CMS neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, we found that the downregulation of ATXN3 in NB cells could increase the expression of both BIM and Bcl-xl. It was reported that AKT inhibitors (perifosine or MK-2206) could promote the BIM expression, but decrease Bcl-xl expression ( 66 , 67 , 84 , 85 ). So, when the ATXN3-down-regulated NB cells were treated with AKT inhibitors (perifosine or MK-2206), the balance between BIM and Bcl-xl may tilt towards BIM, the accumulation of pro-apoptotic BIM may induce more cell death.…”
Section: Discussionmentioning
confidence: 99%
“…39 The phosphoinositide 3-kinase-Akt signaling pathway plays an important role in erythropoiesis and can downregulate apoptosis of erythroblasts. 40 MicroRNA-146a was also suppressed 15-fold in the LCHS/CS group compared with LCHS/CSþBB and naïve rodents. He and colleagues 41 found decreased expression of miR-146a in patients with small intestine ischemia and ischemia reperfusion injury, and determined that improved intestine epithelial cell survival occurs with inhibition of Toll-like receptor 4 and tumor necrosis factor receptor-associated factor-6, leading to decreased nuclear factor kappa light chain enhancer of activated B cells, which has been shown to play a role in early erythroid proliferation and suppression of erythroid specific genes.…”
Section: Discussionmentioning
confidence: 89%